Analisis Risiko dan Strategi Mitigasi pada UMKM Buket Bunga di Lombok: Studi Kasus 10 UMKM Buket Bunga - Candradewi, Ida Ayu Prabashinta; Cahyaningtyas, Susi Retna (Jurnal Ilmiah Global Education, 2025)
Flower bouquet SMEs in Lombok have great growth potential in the creative industry, but face various risks that can affect the sustainability of their business. This study aims to identify the types of risks faced, analyze the main causes of the risks, and formulate mitigation strategies that can be applied by flower bouquet SMEs. The method used in this study is the House of Risk (HOR), which consists of two phases: identification and risk assessment (HOR phase 1) and design of mitigation strategies (HOR phase 2). The results of the study indicate that the main risks faced by flower bouquet SMEs in Lombok include delays in procurement of raw materials, sudden increases in the price of fresh flowers, lack of employee training, and lack of quality control in product delivery. Based on the HOR analysis, the prioritized mitigation strategies include collaborating with more than one supplier, conducting routine training for employees, implementing quality inspection procedures before delivery, diversifying products, and optimizing digital marketing to increase competitiveness. With the implementation of effective mitigation strategies, it is hoped that flower bouquet SMEs in Lombok can increase their business resilience and competitiveness in the creative industry market.